DEVELOPMENT GUIDELINES FOR THE PERFORMANCE ACCORDING TO THE PROFESSIONAL CODE OF ETHICS FOR TEACHERS BASED ON TRISIKKHA IN PANTHANAMIT SCHOOLS GROUP, ANGTHONG PROVINCE - Roykong, Nutsaporn; Klomkul , Lampong; Chaisuk, Peerawat (Journal of Educational Review Faculty of Education in MCU, 2024)
This research article aimed to 1) study the status of teachers’ compliance with the teacher’s code of ethics, 2) study the methods of compliance with the teacher’s code of ethics according to the Tri-sikkh principle, and 3) propose guidelines for compliance with the teacher’s code of ethics according to the Tri-sikkh principle. This research was a mixed-methods research. The quantitative research used a questionnaire with the entire population of 97 administrators and teachers. Data were analyzed by finding percentages, means, and standard deviations. The qualitative research used interviews with key informants. Data were analyzed by content analysis. The research results found that 1) The status of compliance with the teacher’s code of ethics of teachers in the Phatthanamit School Group, Ang Thong Province, was at the highest level overall and in each aspect in all 5 aspects. 2) The methods of compliance with the teacher’s code of ethics according to the Tri-sikkh principle of teachers consisted of (1) Ethics towards oneself, continuous self-development, compliance with rules and regulations, and being a good example. (2) Ethics towards the profession, professional development, being a good member of the organization, and networking. (3) Ethics towards service recipients, showing love and kindness, being a good example, and developing students in all aspects. (4) Ethics towards colleagues, creating good relationships, working together, and exchanging knowledge. (5) Ethics towards society, being a good citizen, developing the community, conserving culture, and 3) Guidelines for developing professional ethics for teachers in accordance with the Trisikkh principle of teachers in the Phatthanamit School Group, Ang Thong Province, were as following: (1) Ethics towards oneself: Emphasizing continuous self-development in terms of knowledge, abilities, and ethics in order to be a good role model for students and other personnel. (2) Ethics towards profession: Emphasizing love and faith in the teaching profession, performing duties with honesty and integrity, and being a good member of professional organizations. (3) Ethics towards service recipients: Emphasizing giving importance to all students and service recipients with love, kindness, and full assistance. (4) Ethics towards fellow professionals: Emphasizing building good relationships with fellow teachers and personnel in the school, working together, and exchanging knowledge. (5) Ethics towards society: Emphasizing participation in community development, environmental conservation, and being a good citizen.